SERUM TRI-IODOTHYRONINE AND THYROXINE PROFILE IN INSULIN TREATED ACYCLIC GOATS - SARATH, T; SUGUNA, K; MEHROTRA, S; ARUNMOZHl, N; AGARWAL, S K; UMASHANKAR, (The Indian Journal of Animal Reproduction, 2023)
The present work was carried out with the objective of estimating of tri-iodothyronine (T3) and thyroxine (T 4)concentrations in insulin treated acyclic goats. Fourteen acyclic goats were randomly divided into two groups, i.e.groupA(control, n::: 7) and group B (insulin treated, n::: 7).Animals of treatment group were injected subcutaneouslywith long acting bovine insulin at 0.2 IU/kg bodyweight, once daily for five consecutive days. All the experimentalgoats were subjected to collection of blood on day O (day of first injection), 4, 8, 12, 16, 20, 24 and day 28.Estimation of T3 and T 4 were carried out by using RIA. The mean values of T3 were significantly higher or on day4, 28 (P < 0.01), 12, 16, 20 and 24 (P
Keywords: Insulin; Tri-iodothyronine; Thyroxine; Acyclic goats